Open your eyes [videorecording (DVD)] - Amenábar, Alejandro, 1972- (Artisan Home Entertainment, 2001)
"In this steamy, intriguingly complex, psychological thriller the line between reality and fantasy is hopelessly blurred. César tries to make sense of his life after a car crash leaves his once-handsome face grotesquely disfigured. After he is placed into a psychiatric penitentiary for a murder he doesn't remember committing, César's only hope is to delve into the depths of his subconscious mind where the answer to ending his living nightmare lies in his dreams"--Container.